TRAINING AND GUIDANCE ON PACKAGING DUWET POLINEMA SWEET TOMATO JAM FOR RESIDENTS OF DUWET VILLAGE, TUMPANG SUBDISTRICT, MALANG DISTRICT - Eny Widiyowati; Baroroh Lestari; Evi Suwarni; Fatkhur Rochman; Alvin Nauval; Prima Beauty Kartikasari (Transpublika Publisher, 2023)
The primary objective of this service activity is to enhance the value of products through effective packaging and product promotion. The community involved in the production of Duwet Polinema Sweet Tomato Jam in Duwet Village, Tumpang Sub-district, Malang Regency, faces a weakness in terms of promoting their products, resulting in limited consumer awareness. Duwet Polinema Sweet Tomato Jam is currently packaged in a very simplistic manner, which fails to capture public attention. To address these challenges, it is crucial to provide assistance and support in terms of packaging and labeling for the Duwet villagers who produce this jam. This intervention will contribute to increased visibility and appeal among potential consumers. To ensure consumer recognition of the Duwet Polinema Sweet Tomato Jam product, it is essential to convey information through branding and labeling. Additionally, to support the sustainability of the Duwet Polinema Sweet Tomato Jam business, it is highly recommended to offer comprehensive assistance in marketing and financial management to the company partners. This issue arises from the partners' lack of knowledge about product packaging. Furthermore, it is imperative for the growth and sustainability of the business to obtain government certifications such as P-IRT licenses and food safety certifications, as these certifications guarantee the quality and safety of the Sweet Tomato Jam.